The role of hypoxia in the pathogenesis of congenital hyperplasia of blood vessels in the head and neck in children (literature review) - I. Yu. Bychkova; Kh. A. Abduvosidov; V. V. Abduvosidov (Acta Biomedica Scientifica)
To date, scientists have found that stress plays an important role in the formation of congenital malformations. It can be caused by the influence of negative environmental factors on the pregnant woman or by her own diseases. One of the consequences of stress is hypoxia. It can be acute and chronic, and can have a negative impact both during pregnancy and during childbirth. They also distinguish local and general hypoxia. The consequences of the negative impact of oxygen deficiency on the embryo and fetus can manifest itself both in utero and after birth, leading to  various kinds of congenital malformations, diseases, and sometimes fetal death, or increase the risk of sudden infant death syndrome. Hyperplasia of blood vessels, the so-called children’s hemangiomas, develops both in utero, especially with chronic fetal hypoxia, and during childbirth. It develops due to insufficient blood supply and oxygen deficiency in various parts of the body, most often in the head and neck. In an embryo under conditions of hypoxia, tachycardia develops – with an increase in heart rate and, if it is ineffective, local vasodilation occurs. Only then, under the condition of continuing hypoxia, does an increase in the number of blood vessels develop. This often leads to the formation of hyperplasia of the blood vessels, the so-called children’s hemangiomas.This pathology is quite common, especially among fair-skinned children, which makes its study, in particular the factors that cause this pathology, relevant today.